THE INFLUENCE OF WORK MOTIVATION AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE IN ONLINE SHOPS IN SURABAYA - Rafsanjani, Moch Aldi Rafsanjani; Ansyah, Eko Hardi (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to examine the influence of work motivation and job satisfaction on employee performance in the context of online shops in Surabaya. Method: Employing a quantitative approach with a correlational design, the research involved 200 employees selected through purposive sampling. Data were analyzed using multiple regression techniques to determine the relationship between the independent variables (work motivation and job satisfaction) and the dependent variable (employee performance). Results: The findings revealed that both work motivation and job satisfaction significantly and positively affect employee performance. Furthermore, their combined contribution plays a substantial role in enhancing employee productivity. Novelty: This study contributes to the growing literature by focusing specifically on the online retail sector in an urban Indonesian setting, highlighting the importance of motivation and satisfaction in shaping performance outcomes. It also suggests that organizational factors such as work environment and company policy are critical elements that indirectly support performance by influencing employee motivation and satisfaction.